A hierarchical synchronized data acquisition network for CBM - Lemke, Frank; Brüning, Ulrich (IEEE transactions on nuclear science, 2013)
This paper focuses on the design and concepts of the hierarchically structured Data Acquisistion (DAQ) network for the Compressed Baryonic Matter (CBM) experiment at the Facility for Antiproton and Ion Research (FAIR) in Darmstadt. Due to the limited physical space and the requirement for a multi TB/s DAQ within the system, this experiment requires compact read-out hardware which provides high bandwidth. Additionally, different detector types must be supported, which requires some flexibility regarding read-out structures and a common synchronization mechanism. Another important goal is to provide hardware that supports an identical interconnection protocol within the complete network to avoid protocol conversions. This led to the design and implementation of modular and unified read-out hardware and firmware.
Date of current version October 09, 2013
Gesehen am 19.01.2022